Hubungan Antara Perilaku Destruktif dan Tindakan Bullying Pada Siswa SMPS ST. Antonius Padua Leworahang Di Kabupaten Flores Timur - Hurit, Anastasia Hala; Upa,, Muhamad Pua; Indrawan, Putu Agus; Saba, Khetye R (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2024)
This study aims to find out the description of destructive behavior, the description of acts of bullying, and the relationship between destructive behavior and acts of bullying in students at SMPS St. Antonius Padua Leworahang in East Flores Regency. Destructive behavior is behavior that is rude, against teachers, and violates school regulations which is caused by emotions, hatred, and lack of self-confidence that are not controlled by students. Bullying is an unpleasant action whether verbally, physically or socially in the real world or in the virtual world that makes someone/others feel uncomfortable, hurt and depressed. This research uses a quantitative approach with descriptive correlation research. This research involved students from SMPS St. Antonius Padua Leworahang, East Flores Regency. The sampling technique in this research used Proportional random sampling. The data collection technique used in this research was a questionnaire, and to analyze the data descriptive and correlation analysis techniques were used with the help of the SPSS version 26 program. The results of the research showed (1) a general picture of destructive behavior at SMPS St. Antonius Padua Leworahang is dominantly in the low category with a percentage of 48% (32 people), (2) students' descriptions of bullying acts are dominantly in the high category with a percentage of 52% (35 people), (3) Between destructive behavior and bullying actions there is a direction positive relationship as shown by the calculated r-value of 0.334 ˃ r-table 0.2257. This data shows that the student's destructive behavior variable also has a relationship with bullying actions among students at SMPS St. Antonius Padua Leworahang in East Flores Regency.